Prime minister's Decree No. 2019 of the year 2016 Amending table (4) of annex (6) of the executive regulations of the environment law issued by Prime minister's Decree No. 338/1995 / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 32/2016